Sociological analysis of socio-pathological phenomena in Svetozar Marković’s work “Serbia in the East” - Milošević Šošo Bilјana (Sociološki pregled, 2026)
In 19th-century Serbia, on the eve of modernization processes, a critical voice emerged pointing to the social, political, and moral deviations of the new order. One of the most significant representatives of this perspective was Svetozar Marković. His work Serbia in the East represents a political and sociological treatise, but also a sharp critique of the injustices and dysfunctions of Serbian society after its liberation from the Ottoman rule. The aim of this paper is, through the application of content analysis and a sociological theoretical framework, to systematize the socio-pathological phenomena described in the work and to present Marković’s reform proposals and vision of social transformation. The analysis shows that his insights remain relevant today, serving as a framework for understanding systemic deviations and the need for ethical responsibility.